REVERSED PHASE-HIGH PERFORMANCE LIQUID CHROMATOGRAPHY METHOD DEVELOPMENT AND VALIDATION OF ATORVASTATIN IN BULK DRUG AND FORMULATION - RAMANA G, VENKATA; G, PAVANI; P, SUPRIYA; LATHA N, MADHAVI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To develop and validate a simple, selective, rapid, precise, and accurate high performance liquid chromatographic (HPLC) method for determination of atorvastatin in bulk and its pharmaceutical formulation product. Method: Reversed phase-HPLC (RP-HPLC) method was performed by a mobile phase consisting mixture of methanol and ammonium acetate buffer (pH 4.5) in the proportion 60:40 v/v. A ZORBAX Eclipse plus C (4.6 mm Ã— 100 mm, 3.5 Î¼) column was used as a stationary phase. HPLC analysis of atorvastatin was carried out at a wavelength of 241 nm with a flow rate of 1 ml/minute. 18 Results: The linear regression analysis data for the calibration curve showed a good linear relationship with a correlation coefficient 0.9984. The linear regression equation was y=3726540.2x+27390388.1. This was found to give a sharp peak of atorvastatin at a retention time of 2.77 minutes. Validation parameters were evaluated for the method according to the ICH (Q2R1) guidelines. The limit of detection and limit of quantification for the method were 0.6721 Î¼g/mL and 1.9989 Î¼g/mL, respectively. The % relative standard deviation values for intra-day precision and inter-day precision were found to be 0.31% and 0.30%, respectively. An accuracy of the method was determined through recovery studies which were found to be within 97.57-102.22%. Conclusion: The method was validated for system suitability, accuracy, precision, robustness, and ruggedness. The precision, accuracy, sensitivityshort retention time and composition of the mobile phase indicated that this method is better than the earlier methods developed for the quantification of atorvastatin. Keywords: Atorvastatin, Reversed phase-high performance liquid chromatographic method development, Validation.